Linking microbial diversity and functionality of arctic glacial surface habitats. (30th August 2016) - Lutz, Stefanie; Anesio, Alexandre M.; Edwards, Arwyn; Benning, Liane G.
Summary: Distinct microbial habitats on glacial surfaces are dominated by snow and ice algae, which are the critical players and the dominant primary colonisers and net producers during the melt season. Here for the first time we have evaluated the role of these algae in association with the full microbial community composition (i.e., algae, bacteria, archaea) in distinct surface habitats and on 12 glaciers and permanent snow fields in Svalbard and Arctic Sweden. We cross‐correlated these data with the analyses of specific metabolites such as fatty acids and pigments, and a full suite of potential critical physico‐chemical parameters including major and minor nutrients, and trace metals. It has been shown that correlations between single algal species, metabolites, and specific geochemical parameters can be used to unravel mixed metabolic signals in complex communities, further assign them to single species and infer their functionality. The data also clearly show that the production of metabolites in snow and ice algae is driven mainly by nitrogen and less so by phosphorus limitation. This is especially important for the synthesis of secondary carotenoids, which cause a darkening of glacial surfaces leading to a decrease in surface albedo and eventually higher melting rates.